Johrei Family Healing: A Pilot Study. Issue 4 (2006) - Canter, P. H.; Brown, L. B.; Greaves, C.; Ernst, E.
Abstract : Johrei is a form of spiritual healing comprising "energy channelling" and light massage given either by a trained healer or, after some basic training, by anyone. This pilot trial aimed to identify any potential benefits of family-based Johrei practice in childhood eczema and for general health and to establish the feasibility of a subsequent randomised controlled trial. Volunteer families of 3-5 individuals, including at least one child with eczema were recruited to an uncontrolled pilot trial lasting 12 months. Parents were trained in Johrei healing and then practised at home with their family. Participants kept diaries and provided questionnaire data at baseline, 3, 6 and 12 months. Eczema symptoms were scored at the same intervals. Scepticism about Johrei is presently an obstacle to recruitment and retention of a representative sample in a clinical trial, and to its potential use in general practice. The frequency and quality of practise at home by families may be insufficient to bring about the putative health benefits. Initial improvements in eczema symptoms and diary recorded illness, could not be separated from seasonal factors and other potential confounders. There were no improvements on other outcomes measuring general health and psychological wellbeing of family members.